REVISITING THE RELATION BETWEEN ENVIRONMENTAL PERFORMANCE AND FINANCIAL PERFORMANCE - Rizqy Aiddha Yuniawati (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2020)
This study aims to determine the effect of environmental performance on corporate financial performance. The method used in this research is a descriptive research method with a quantitative approach. The population in this study are textile companies listed on the Indonesia Stock Exchange. The sampling technique in this study uses purposive sampling, which is a textile company that is listed on the Indonesia Stock Exchange and publishes financial statements in 2017-2018 and has participated in the Company Performance Rating Program. The type of data used is secondary data with the documentation data collection method from the official website of the Indonesia Stock Exchange. The analysis tool used is linear regression. Environmental performance is measured by the company's performance in the PROPER (environmental performance rating program in environmental management). Financial performance is measured by returns on assets (ROA). Based on research result, it can be concluded that environmental performance has not significant effect on the company's financial performance. This study contributes to the environmental accounting literature especially for sustainable development. This study is expected to provide considerations to further increase awareness of environmental performance by making accurate disclosure principles.